People's participation in development - A critical analysis - Bajpai, P.K. (1998)
Highly critical of the present model of people's participation in development in India, the author points to emergence of some dangerous trends in our political system rooted therein. With this background, he discusses the realities of people's participation in major rural development programmes to assert elusiveness of people's participation that was visualised behind it. He then gives a critical commentary on the subject, identifying significant factors responsible therefor. Before summing up the discussion, he gives a 7-point package which possibly could ensure real people's participation in development in India. - Reproduced
Keywords: Rural development - India; Rural development